Iron-Incorporated Activated Carbon Synthesis from Biomass Mixture for Enhanced Arsenic Adsorption - Rahman, Hawraz Luqman; Erdem, Hatice; Sahin, Mehmet; Erdem, Mehmet (Springer Int Publ Ag, 2020)
This study discusses synthesis and characterization of iron-incorporated activated carbon (MAC) from biomass mixture by FeSO4 impregnation and subsequently pyrolysis, and its application in arsenic adsorption from aqueous solution. The textural, morphological, and structural properties were determined with BET surface area, total pore volume, average pore size, pH(pzc), XRD, VSM, and SEM-EDX analysis. The results showed that the MAC has 375.32 m(2)/g surface area and 0.2391 cm(3)/g of total pore volume and contains a single iron compound in the magnetite structure. Arsenic removal efficiency was evaluated depending on MAC dosage, pH, contact time, and As(V) concentration. The data was analyzed by Freundlich and Langmuir isotherms. Also, pollution potential of the adsorption residue was examined by TCLP. 10 mg/l of As(V) in the solution could be removed in the presence of 1.5 g/l of MAC at pHs above 2.5 for 60 min. As(V) adsorption fitted better to the Langmuir isotherm, and adsorption capacity was found to be 42.92 mg/g. It has been found that the adsorption residue has no potential pollutants; thus, they are safe for regular landfill waste disposal. The results suggested that FeSO4 impregnation and subsequently pyrolysis were suitable process for synthesis of MAC from biomasses for arsenic adsorption.
Keywords: Arsenic removal; Iron incorporation; Activated carbon; Biomass; Chemical activation